Knock-down of the 37kDa/67kDa laminin receptor LRP/LR impedes telomerase activity. - Naidoo, K.; Malindisa, S.T.; Otgaar, T.C.; Da Costa Dias, B.; Ferreirra, E.; Reusch, U.; Knackmuss, S.; Little, M.; Weiss, S.F.T.; Letsolo, B.T. (Public Library of Science., 2015)
Cancer has become a major problem worldwide due to its increasing incidence and mortality rates. Both the 37kDa/67kDa laminin receptor (LRP/LR) and telomerase are overexpressed in cancer cells. LRP/LR enhances the invasiveness of cancer cells thereby promoting metastasis, supporting angiogenesis and hampering apoptosis. An essential component of telomerase, hTERT is overexpressed in 85-90% of most cancers. hTERT expression and increased telomerase activity are associated with tumor progression. As LRP/LR and hTERT both play a role in cancer progression, we investigated a possible correlation between LRP/LR and telomerase. LRP/LR and hTERT co-localized in the perinuclear compartment of tumorigenic breast cancer (MDA-MB231) cells and non-tumorigenic human embryonic kidney (HEK293) cells. FLAG® Co-immunoprecipitation assays confirmed an interaction between LRP/LR and hTERT. In addition, flow cytometry revealed that both cell lines displayed high cell surface and intracellular LRP/LR and hTERT levels. Knock-down of LRP/LR by RNAi technology significantly reduced telomerase activity. These results suggest for the first time a novel function of LRP/LR in contributing to telomerase activity. siRNAs targeting LRP/LR may act as a potential alternative therapeutic tool for cancer treatment by (i) blocking metastasis (ii) promoting angiogenesis (iii) inducing apoptosis and (iv) impeding telomerase activity.
Keywords: laminin receptor;; small interfering RNA;; telomerase;; breast cancer;; cancer cell line;; cell level;; cell nucleus;; cell surface;; controlled study;; embryo;; enzyme activity;; gene silencing;; HEK293 cell line;; human; human cell;; MB231 cell line;; protein function;; protein localization;; protein protein interaction;; RNA interference;